A phase 2, double-blind, placebo-controlled trial of a valproate/lithium combination in ALS patients - M.-C. Boll; M. Alcaraz-Zubeldia; C. Rios; D. González-Esquivel; S. Montes (Neurología (English Edition))
Background: Few treatments are currently available for amyotrophic lateral sclerosis (ALS). A combination of lithium carbonate and valproic acid (VPA-Li) was shown to inhibit motor neuron death and delay disease progression. Methods: Outpatients with a typical ALS presentation were enrolled in a randomized, placebo-controlled trial to assess the efficacy of orally administered VPA-Li. Changes in a functional scale score (ALSFRS-R) and survival rate were chosen as primary outcome variables. Secondary outcome variables included BMI, respiratory monitoring, quality of life, and a global impression of the treatment. Results: Out of 42 patients enrolled, 20 individuals receiving VPA-Li and 18 on placebo treatment were included in the final analysis. Forty-five percent of patients receiving VPA-Li completed the trial, whereas only 22.22% of patients in the placebo group attended the final visit 18 months later (P = 0.09). Major changes in the ALSFRS-R score were observed, including a decrease of 1.195 points/month in the placebo group (95% CI: 0.7869–1.6031) and of 0.5085 under VPA-Li treatment (95% CI: 0.2288–0.7882) between months 6 and 14. Adverse events included bad mouth taste, constipation, and anorexia. Survival rate, body weight, and quality of life were positive outcomes by the end of the trial despite a high sample reduction, especially in the placebo group. The inclusion of 212 subjects in each group would confirm these differences. Conclusions: Combined VPA-Li treatment associated with slower ALS progression and better secondary outcomes. This dual treatment overcame the futility threshold and merits further investigation in ALS. Resumen: Fundamentos: Contamos actualmente con pocos tratamientos para la esclerosis lateral amiotrófica (ELA), Se demostró que una combinación de carbonato de litio y ácido valproico (VPA-Li) inhibe la muerte de las motoneuronas y enlentece la progresión de la enfermedad. Métodos: Pacientes ambulatorios con un cuadro típico de ELA se incluyeron en un ensayo clínico aleatorizado controlado con placebo para evaluar la eficacia de VPA-Li administrado por vía oral. Los cambios en la escala funcional (ALSFRS-R) y la tasa de sobrevida constituyeron los desenlaces primarios. Las variables de desenlace secundario fueron el Índice de masa corporal, el monitoreo de la función respiratoria, la calidad de vida y la impresión global del tratamiento. Resultados: De los 42 pacientes incorporados, 20 que recibieron VPA-LI y 18 el placebo, se incluyeron en el análisis final. En total, el 45% de los pacientes tratados con VPA-Li completaron el ensayo, mientras que solo el 22.22% de los del grupo placebo asistieron a la visita final, 18 meses después (p = 0,09). Se observaron como cambios en la ALSFRS-R, una disminución de 1,195 puntos/mes en el grupo de placebo (IC del 95%: 0,7869–1,6031) y de 0,5085 en el tratamiento con VPA-Li (IC del 95%: 0,2288–0,7882), entre los meses 6 y 14. Entre raros eventos adversos se registraron mal sabor de boca, estreñimiento y anorexia. La tasa de supervivencia, el peso corporal y la calidad de vida fueron resultados positivos al final del ensayo a pesar de la reducción de la muestra, especialmente en el grupo placebo. La inclusión de 212 sujetos en cada grupo confirmaría estas diferencias. Conclusiones: Un tratamiento combinado de VPA-Li se vinculó con una progresión más lenta de la ELA y con un mejor desenlace secundario. Este tratamiento dual superó el umbral de futilidad y merece una mayor investigación en ELA.